Saint Lucia. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Saint Lucia during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as technologies, automation, trade, agribusiness, financing, packaging, labeling, rural development, nutrition and resilience. against climate change. Finally, healthy consumption, improvement of quality standards, training, inclusion of women in agriculture and in the pineapple and vegetable value chains were supported.